Solid waste impact on the use of natural resources - Nik-Wan, Nik Zam (Universiti Teknologi MARA, Kelantan, 2018)
Among other types of waste, municipal solid waste is commonly encountered and rapidly generated since it includes everyday items that are discarded by the public mainly household and commercial sectors. Increasing number of population has made it worst since it contributes further to the generation of more and more waste. In areas where recycling activities are not the norm of the society, the municipal solid waste will consist of numerous types of waste which are dumped together yet it cannot be destroyed in one similar way. Open dumping, open burning as well as landfills are among the unsustainable techniques commonly practices in Malaysia. Improper waste management system creates environmental impacts which are irreversible most of the time. This conceptual paper aims to highlight the significant impacts of the solid waste management to the use of natural resources and to suggest alternative waste management system that would minimize environmental impacts. It is hoped that the outcome of this paper could create greater environmental awareness of the society that would entice environmental friendly behavior leading to sustainable waste management system.